Virus genomics and evolution: the transformative effect of new technologies and multidisciplinary collaboration on virus research and outbreak management. Issue 1 (December 2016) - Ip, Camilla; Pybus, Oliver; Gardy, Jennifer
Abstract The first Virus Genomics and Evolution Conference was held at the Wellcome Genome Campus in Hinxton, UK, 8–10 June 2016.